PENGEMBANGAN MODEL MANAJEMEN PELATIHAN METODE EKSPRESI BEBAS BERBASIS ANAK DALAM RANGKA MENGEMBANGKAN POTENSI KREATIF ANAK TK DENGAN OPTIMAL - Kamsijo Kamsijo (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2014)
The aims of the research are to show that: 1. Training program is effective to prepare kindigarten teachers professionally mastering method, material, making preparation, conducting and evaluating teaching learning process especially to develop creative drawing potential for golden age students optimally. 2. By using free expression method will very support condusive situation for drawing activity the golden age students to develop optimally. 3. By preparing a training model of free expression method that is based on children for kindigarten teachers that is conducted professionally with closed attention to training management principals accurately and measurable, so that it will guarantee the formed of kindigarten teachers professionally. Therefore, the development of it needs more ideas and opinion from kindigarten teachers/members of training for material and everything that are needed for training. The existing training model to be based for development as in line with field needed. For innovation of training management model we need Research and Development (RD). This research is for developing, resulting product and examining the qualified product. Longitudinally, stages multi years, to applicate descriptive method. a. Need analysis, b. Evaluative, c. Experiment. Study result showed that the existing drawing training model has not handled professionally, it did not applicate management principal correctly, such as: planning, organizing, conducting, evaluating and follow up. It conducted insidentally, top down, no inisiative from training participants, no pretest and pos test and no monitoring/follow up. The research result showed that kindigarten teachers are badly needed the existing of training model of free expression method based on children that is managed professionally. It needed quality process and training result, mainly its procedure and conducting. Training media should be practical and can be used easily. Training target should be clear for creative drawing with conservation topic that is supported by qualified literatures for traning and teachers.